Love your job : the new rules of career happiness - Hannon, Kerry (John Wiley & Sons, Inc., 2015)
"Yes, it is possible to have a job you love, and it doesn't require starting from scratch. Love Your Job is a guide to making work fulfilling and fun again, or even for the first time. Why count down the hours of the day or the days to retirement when you could reinvigorate your workday, transforming the daily doldrums into a daily dose of enjoyable activity? Kerry Hannon, The New York Times columnist and AARP's Jobs Expert, focuses on the little things that can make a big difference in how we feel about work. Love Your Job is all about the routines, habits, and thought patterns that, over the years, may have turned a dream job into a drudge or, worse, a nightmare. Changing these habits and attitudes is simple, and this book shows you how to identify the little things that make work enjoyable and engaging."--